Synthesis and anticancer evaluation of novel 9α-substituted-13-(1, 2, 3-triazolo)-parthenolides. Issue 24 (15th June 2016) - Zaki, Mohamed; Allouchi, Hassan; El Bouakher, Abderrahman; Duverger, Eric; El Hakmaoui, Ahmed; Daniellou, Richard; Guillaumet, Gérald; Akssira, Mohamed
Graphical abstract: Highlights: 9α-Hydroxyparthenolide was obtained from the plant Anvillea radiata . Regio- and stereoselective synthesis of new C9- and C13-substituted parthenolides. 9α-Hydroxyparthenolide derivatives were tested for their in vitro anticancer activity. Abstract: A series of novel 9α-substituted-13-(1, 2, 3-triazolo)-parthenolides3 –20 were efficiently synthesized and tested for their in vitro anticancer activity using the MTT colorimetric assay against four human cancer cell lines. 9α-Substituted-13-(1, 2, 3-triazolo)-parthenolide derivatives were prepared by the diastereoselective Michael addition of TMSN3 onto 9α-hydroxyparthenolide1 to give the key intermediate 9α-trimethylsilyloxy-13-(1, 2, 3-triazolo)-parthenolide2 which was utilized in a regioselective Huisgen 1, 3-dipolar cycloaddition reaction with various alkynes to afford 1, 4-disubstituted-1, 2, 3-triazoles of 9α-substituted-parthenolide.